PEMBERDAYAAN DESA PRIMA SENDANGAGUNG: MENGELOLA DAN MEMASARKAN PRODUK BERBASIS LELE - Mohamad Irhas Effendi; Bambang Sugiarto; Jubaedah Nawir (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Sendangagung Village is one of the villages in Sleman which has several catfish farms to help the community's economy. Besides being cheap and easy to get, catfish has a variety of nutrients that are good for the body. However, in catfish farming, it is not an easy thing. Because there are so many farmers who actually experience losses in catfish farming because the selling price is too low. In addition, there is a Desa Prima consisting of Sendangagung women, an alternative or breakthrough in efforts to empower women in the economy through increasing women's empowerment and increasing income women, especially poor families. This service intends to combine the two groups above to solve common problems, namely the Catfish Farmer Group and Desa Prima Sendangagung through four stages, namely program socialization, mentoring, education and training, and post-training partner monitoring. Desa Prima Sendangagung will obtain relatively cheap raw materials which will be processed into various products and sold online. Meanwhile, catfish farmers will benefit from having no trouble marketing their crops.